Prevalence of Abuse and Violence Before, During, and After Pregnancy in a National Sample of Canadian Women - Daoud, Nihaya (American Public Health Association, 2012)
Objectives. We describe the prevalence of abuse before, during, and after pregnancy among a national population-based sample of Canadian new mothers. Methods. We estimated prevalence, frequency, and timing of physical and sexual abuse, identified category of perpetrator, and examined the distribution of abuse by social and demographic characteristics in a weighted sample of 76 500 (unweighted sample = 6421) Canadian mothers interviewed postpartum for the Maternity Experiences Survey (2006–2007). Results. Prevalence of any abuse in the 2 years before the interviews was 10.9% (6% before pregnancy only, 1.4% during pregnancy only, 1% postpartum only, and 2.5% in any combination of these times). The prevalence of any abuse was higher among low-income mothers (21.2%), lone mothers (35.3%), and Aboriginal mothers (30.6%). In 52% of the cases, abuse was perpetrated by an intimate partner. Receiving information on what to do was reported by 61% of the abused mothers. Conclusions. Large population-based studies on abuse around pregnancy can facilitate the identification of patterns of abuse and women at high risk for abuse. Before and after pregnancy may be particularly important times to monitor risk of abuse.